Analisis Perbandingan Penerapan Budaya Etika Pancasila dengan Sistem Budaya Barat Di Indonesia - Pasaribu, Anissya Fahira; Usiono Usiono (LPPM Politeknik Pratama, 2024)
In this era leading to the industrial revolution 5.0, we are becoming increasingly aware of the magnitude of the western cultural system that has entered Indonesia, which is causing the Pancasila ethical culture to fade in this country. Therefore, the author wants to analyze how much the implementation of the Pancasila ethical culture compares with the western cultural system. in Indonesia. This type of research is qualitative with a Systematic Literature Review (SLR) analysis method that is relevant to the title of the research. Then the researcher also conducted interviews with the generation in the 5.0 era. From the results of findings and studies from various sources, it was found that 65% of the generation in the 5.0 era applied more of the cultural system. western than Pancasila ethical culture, this is because the influence of the social sphere and the flow of technology received mostly comes from the western cultural system. The solution that must be taken to improve Pancasila cultural ethics is to carry out a Pancasila campaign, strengthening cultural networks by providing a platform to display and promote traditional Indonesian arts and culture.